1996
DOI: 10.1016/s0092-8674(00)81237-4
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking p27 Display Increased Body Size, Multiple Organ Hyperplasia, Retinal Dysplasia, and Pituitary Tumors

Abstract: Mice lacking p27(Kip1) have been created by gene targeting in embryonic stem cells. These mice are larger than the control animals, with thymus, pituitary, and adrenal glands and gonadal organs exhibiting striking enlargement. CDK2 activity is elevated about 10-fold in p27(-/-) thymocytes. Development of ovarian follicles seems to be impaired, resulting in female sterility. Similar to mice with the Rb mutation, the p27(-/-) mice often develop pituitary tumors spontaneously. The retinas of the mutant mice show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

72
1,142
6
13

Year Published

1997
1997
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,482 publications
(1,233 citation statements)
references
References 55 publications
72
1,142
6
13
Order By: Relevance
“…The importance of p27 Kip1 in the regulation of T-cell proliferation Nourse et al, 1994) has also been con®rmed by studies on p27 Kip1 -null mice (Fero et al, 1996;Kiyokawa et al, 1996;Nakayama et al, 1996). These animals were presented with increased proliferation of thymocytes, resulting in thymic hyperplasia and an increased responsiveness of splenic and thymic T-cells to IL-2, which, in turn, correlated with higher cyclin E-associated kinase activity.…”
Section: Discussionmentioning
confidence: 89%
“…The importance of p27 Kip1 in the regulation of T-cell proliferation Nourse et al, 1994) has also been con®rmed by studies on p27 Kip1 -null mice (Fero et al, 1996;Kiyokawa et al, 1996;Nakayama et al, 1996). These animals were presented with increased proliferation of thymocytes, resulting in thymic hyperplasia and an increased responsiveness of splenic and thymic T-cells to IL-2, which, in turn, correlated with higher cyclin E-associated kinase activity.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, p27 KIP1 declines in the presence of mitogenic growth factor signalling or interleukin-2 (Nourse et al, 1994;Cheng et al, 1998). p27 KIP1 -deficient mice develop a variety of abnormalities including multiorgan hyperplasia and pituitary tumours (Nakayama et al, 1996). Furthermore, the higher the levels of p27 KIP1 expression, the better the prognosis with regard to human malignant gliomas (Alleyne et al, 1999), breast cancer (Porter et al, 1997) or lung cancer (Esposito et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the role of p27 in prostate disease includes the observation that knockout mice with a p27À/À genotype demonstrate histologic benign prostatic hyperplasia. 16 Kyprianou's group has shown loss of p27 in prostatic carcinoma as well as the important observation that this loss is associated with higher proliferative activity and higher tumor grade. 17 Cordon-Cardo et al 18 have demonstrated loss of p27 in prostatic carcinoma, as well as diffuse p27 staining in normal prostate epithelium and a distinct absence of staining in BPH nodules.…”
Section: Discussionmentioning
confidence: 99%